Atlantic multidecadal variability control on European sea surface temperatures is mainly externally forced - L Barghorn; F Börgel; M Gröger; H E M Meier (Environmental Research Letters, 2025)
The semi-enclosed European seas (Baltic Sea, North Sea, Mediterranean Sea, and Black Sea) have been among the fastest warming seas worldwide during the last decades. Projections of future temperature trends can provide essential information for decision makers, but they are subject to a number of uncertainties. One important source of uncertainty is the rather high internal climate variability in that region. Separating internal variability and forced trends is therefore paramount. Particularly powerful tools for this separation are Single-Model Initial-condition Large Ensembles (SMILEs). In such ensembles, the same model is run multiple times with similar forcing but varying initial conditions, resulting in different realizations of internal variability. This study employs two SMILEs to decompose European sea surface temperatures (SSTs) into forced trends and internal variability and to investigate whether and how the latter is affected by the Atlantic multidecadal variability (AMV) in the historical period and different future emission scenarios. It is shown that on a decadal scale, the effect of the AMV on the European SSTs will stay important, especially in lower emission scenarios. However, on longer time scales, forced trends will be much higher and in all but the lowest emission scenario considered, more than 2 $\,^°$ C warming compared to 1950 are very likely to be reached until the end of the century in all semi-enclosed European seas.